2021
DOI: 10.1186/s12951-021-00825-4
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical applications of 2D monoelemental materials formed by group VA and VIA: a concise review

Abstract: The development of two-dimensional (2D) monoelemental nanomaterials (Xenes) for biomedical applications has generated intensive interest over these years. In this paper, the biomedical applications using Xene-based 2D nanomaterials formed by group VA (e.g., BP, As, Sb, Bi) and VIA (e.g., Se, Te) are elaborated. These 2D Xene-based theranostic nanoplatforms confer some advantages over conventional nanoparticle-based systems, including better photothermal conversion, excellent electrical conductivity, and large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 124 publications
0
26
0
Order By: Relevance
“…The synthesis/fabrication of 2D materials can be mainly categorized as two top-down and bottom-up methods. The top-down method relies on mechanical forces to destroy the weak van der Waals interaction between layers to obtain a single or multilayer nanometer sheets, such as mechanical cleavage and liquid exfoliation [ 1 , 10 , 41 ].…”
Section: Design and Synthesis Of 2d Nanomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis/fabrication of 2D materials can be mainly categorized as two top-down and bottom-up methods. The top-down method relies on mechanical forces to destroy the weak van der Waals interaction between layers to obtain a single or multilayer nanometer sheets, such as mechanical cleavage and liquid exfoliation [ 1 , 10 , 41 ].…”
Section: Design and Synthesis Of 2d Nanomaterialsmentioning
confidence: 99%
“…In direct liquid exfoliation, the bulk crystal is firstly dispersed in a specific medium such as dimethylformamide (DMF) or N-methyl-pyrrolidone (NMP). Under sonication, the ultrasonic wave can generate cavitation bubbles and high-speed microjets through hydroxyl radical or pyrolysis reaction on the surface of the crystal [ 1 ]. Then, tensile forces appear to remove the van der Waals force between the layers.…”
Section: Design and Synthesis Of 2d Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two‐dimensional (2D) materials such as photothermal therapeutic agents have found a wide of applications in nanomedicine. [ 46–57 ] Black phosphorus (BP), is an emerging 2D crystalline material with a unique layered structure, holding great promise for bone regeneration due to its excellent biocompatibility, adjustable bandgap, and high photothermal conversion efficiency. [ 58–62 ] Therefore, BP has been widely applied in the fields of cancer therapy, anti‐inflammation, and bone regeneration using the high‐efficiency photothermal conversion of BP under near‐infrared (NIR) irradiation (Figure 4A).…”
Section: Perspectivesmentioning
confidence: 99%
“…2,3 In the following decade, many of the emerging 2D nanomaterials such as monoelemental germanene, 4 xene, 5 stanine 6 and so on were synthesized and used in bioengineering. [7][8][9][10] In 2014, Li et al reported for the first time layered nanoscale black phosphorus (NBP) from a silica substrate. 11 The direct band gap of 2D NBP can be adjusted by tailoring its composition and it has been used for improving the performance of photodetectors 12,13 and photoelectric sensors.…”
Section: Introductionmentioning
confidence: 99%